2020
DOI: 10.1681/asn.2020020190
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Vasopressin Type-2 Receptors Regulate Myofibroblasts by a YAP-CCN2–Dependent Mechanism in Polycystic Kidney Disease

Abstract: BackgroundFibrosis is a major cause of loss of renal function in autosomal dominant polycystic kidney disease (ADPKD). In this study, we examined whether vasopressin type-2 receptor (V2R) activity in cystic epithelial cells can stimulate interstitial myofibroblasts and fibrosis in ADPKD kidneys.MethodsWe treated Pkd1 gene knockout (Pkd1KO) mice with dDAVP, a V2R agonist, for 3 days and evaluated the effect on myofibroblast deposition of extracellular matrix (ECM). We also analyzed the effects of conditioned me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…The CCN matricellular proteins have been implicated in induction of senescence in a variety of contexts (Joon-Il Jun & Lau, 2011; Joon-II Jun & Lau, 2017; Valentijn et al, 2021). They are also regulatory targets of the YAP/TAZ pathway, a mechanosensing pathway recently highlighted for its potential role in fibrosis (Dwivedi et al, 2020; Mascharak et al, 2022; Zhou et al, 2022). Activation of YAP was associated with increased fibrosis, increased expression of CSF1 leading to myeloid-derived inflammation, and increased expression of CCN family members.…”
Section: Discussionmentioning
confidence: 99%
“…The CCN matricellular proteins have been implicated in induction of senescence in a variety of contexts (Joon-Il Jun & Lau, 2011; Joon-II Jun & Lau, 2017; Valentijn et al, 2021). They are also regulatory targets of the YAP/TAZ pathway, a mechanosensing pathway recently highlighted for its potential role in fibrosis (Dwivedi et al, 2020; Mascharak et al, 2022; Zhou et al, 2022). Activation of YAP was associated with increased fibrosis, increased expression of CSF1 leading to myeloid-derived inflammation, and increased expression of CCN family members.…”
Section: Discussionmentioning
confidence: 99%
“…Shome et al recently reported that dermal fibroblasts activation of YAP stimulates CCN2 secretion, which in turn through paracrine signaling activates keratinocytes, accelerate migration, and promote wound healing (Shome et al, 2020). Conversely, cystic epithelial cells stimulate myofibroblast activation in the pericystic microenvironment leading to fibrosis through activation of YAP and stimulation of CCN2 expression (Dwivedi et al, 2020). It also should be noted that YAP/TAZ-CCN2 axis may function as an important mediator in fibrosis through myofibroblast activation and ECM production.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Based on our previous results regarding the modulation of intracellular signalling pathways by PC1 and HP in GBM cells, we wondered whether PC1 blockade and/or HP may also affect the levels of proteins involved in the regulation of gene transcription within the GBM cell nucleus. Specifically, we decided to focus on two well‐known mechano‐induced transcription cofactors, namely, YAP and TAZ because both have been identified as mediators of PC1‐dependent mechanotransduction 31–35 and are implicated in GBM pathogenesis 36 5).…”
Section: Resultsmentioning
confidence: 99%